2010
DOI: 10.1103/physrevb.82.174427
|View full text |Cite
|
Sign up to set email alerts
|

Probing the magnetic ground state of the molecular dysprosium triangle with muon spin relaxation

Abstract: We present zero field muon spin lattice relaxation measurements of a Dysprosium triangle molecular magnet. The local magnetic fields sensed by the implanted muons indicate the coexistence of static and dynamic internal magnetic fields below T * ∼ 35 K. Bulk magnetization and heat capacity measurements show no indication of magnetic ordering below this temperature. We attribute the static fields to the slow relaxation of the magnetization in the ground state of Dy3. The fluctuation time of the dynamic part of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
(37 reference statements)
0
22
0
Order By: Relevance
“…of the quasi-static nature of the local fields experienced by the implanted muons, i.e., the local field is predominantly static with a smaller dynamic component. In this case the relaxation can be described using a phenomenological function; a Lorentzian Kubo-Toyabe (LKT) multiplied by an exponential 21 . The LKT accounts for the relaxation due to the distribution of static fields while the exponential accounts for the depolarization due to the small dynamic component.…”
Section: µSr Measurementsmentioning
confidence: 99%
“…of the quasi-static nature of the local fields experienced by the implanted muons, i.e., the local field is predominantly static with a smaller dynamic component. In this case the relaxation can be described using a phenomenological function; a Lorentzian Kubo-Toyabe (LKT) multiplied by an exponential 21 . The LKT accounts for the relaxation due to the distribution of static fields while the exponential accounts for the depolarization due to the small dynamic component.…”
Section: µSr Measurementsmentioning
confidence: 99%
“…This was the first detection of a toroidal moment in a molecular system, which caused its intensive study, first of all, in the original Dy 3 triangle. [29][30][31][32] In particular, investigations of the magnetoelectric properties of this compound revealed specific magnetoelectric and magneto-current effects related to its toroidal moment. 33,34 It was shown that this molecule is rather rich and versatile for manipulation by external electric and magnetic fields or just by current.…”
Section: Introductionmentioning
confidence: 99%
“…The dysprosium-based compound exhibits a slow relaxation of magnetization with a blocking temperature of 3 K at 1500 Hz with an energy barrier of 33 K, which is a typical feature of single molecule magnets (SMMs). 27,30,31 With regard to a similar structural motif, an iso-propoxide-bridged dysprosium square-based pyramid [Dy 5 O(OiPr) 13 ] exhibiting a slow magnetic relaxation at temperatures as high as 40 K was prepared recently. 32 The thermal energy barrier to relaxation of magnetization of this single-molecule magnet is 530 K.…”
Section: Introductionmentioning
confidence: 99%